2019
DOI: 10.1111/dth.12781
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional triamcinolone alone or in combination with botulinium toxin A is ineffective for the treatment of formed keloid scar: A double blind controlled pilot study

Abstract: Cutaneous injury can ignite excessive fibroproliferative growth that results in keloid formation. Keloids are associated with significant morbidity related to disfigurement and/or symptoms (e.g., pain and pruritus). First‐line treatment of formed keloids involves topical or intralesional steroids. Recurrent or resistant keloids are managed by surgical excision or cryotherapy, followed by steroidal application or adjuvant irradiation. Although adjuvant irradiation appears to be most efficacious, alternative the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 29 publications
1
47
0
Order By: Relevance
“…Data has been mixed, however, as to how botulinum toxin compares to steroid injections. While studies such as those by Shaarawy et al and Rasaii et al found no difference between the two treatments, Pruksapong et al found steroids to be superior, while a metanalysis performed by Bi et al showed botulinum toxin as superior [23][24][25][26]. Factors such as decreased adverse effects and greater improvement in symptoms offer additional benefits of botulinum toxin in comparison to triamcinolone [23,24].…”
Section: Botulinum Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Data has been mixed, however, as to how botulinum toxin compares to steroid injections. While studies such as those by Shaarawy et al and Rasaii et al found no difference between the two treatments, Pruksapong et al found steroids to be superior, while a metanalysis performed by Bi et al showed botulinum toxin as superior [23][24][25][26]. Factors such as decreased adverse effects and greater improvement in symptoms offer additional benefits of botulinum toxin in comparison to triamcinolone [23,24].…”
Section: Botulinum Toxinmentioning
confidence: 99%
“…While studies such as those by Shaarawy et al and Rasaii et al found no difference between the two treatments, Pruksapong et al found steroids to be superior, while a metanalysis performed by Bi et al showed botulinum toxin as superior [ 23 26 ]. Factors such as decreased adverse effects and greater improvement in symptoms offer additional benefits of botulinum toxin in comparison to triamcinolone [ 23 , 24 ]. Recent work using botulinum toxin in a mouse keloid model showed decreased Ki-67 (denoting decreased cell proliferation) as well as fewer and less haphazardly arranged collagen bundles, findings which were comparable to treatment of their mouse keloid model with steroid injections [ 27 ].…”
Section: Injectionsmentioning
confidence: 99%
“…BTXA is available for clinical use in a number of countries as its safe and has effective properties in the treatment of hypertrophic scarring (20). Rasaii reported that triamcinolone in combination with BTXA was ineffective for keloid scars (21), while BTXA was demonstrated to attenuate HS growth and improve the symptoms of HS in clinical practice (22). Currently, an increasing number of studies have demonstrated that BTXA can alleviate fibrosis by regulating fibroblast behaviors in HS and capsular contracture.…”
Section: Introductionmentioning
confidence: 99%
“…Another blind study compared the effect of triamcinolone acetonide (maximum of 40 mg dose) plus pla-cebo versus triamcinolone acetonide and botulinum toxin (20IU) for keloid scars injected every four weeks for a total of 12 weeks. Although the difference in height, vascularization, and the pliability were not significant between the two groups, there was a significant difference in favour of the botulinum group in terms of pain and pruritus control ((p < 0.001) at the end of the study [112].…”
Section: Botulinum Toxinmentioning
confidence: 72%